DETECTION OF MODIFIED LIPOPROTEINS IN ATHEROSCLEROTIC LESIONS OF HUMAN AORTA - P. V. Pigarevsky; O. Yu. Archipova; A. D. Denisenko (Медицинская иммунология)
Abstract. Specific autoantibodies against acetylated, maleylated and malonic dialdehyde-(MDA)-modified lipoproteins are detectable in human plasma. Immunization of rabbits with autologous, correspondingly modified low-density lipoproteins (LDLs) did induce autoantibodies against acetylated, maleylated and MDA-modified lipoproteins. In atherosclerotic lesions from hyman aorta, the epitopes have been detected that were recognized by the antibodies to acetylated, maleylated, and MDA-modified LDLs. Such antigens were detected at all atherogenesis stages, beginning with the earliest lesions (lipid spots), and their deposition pattern was quite variable.Rabbit and human autoantibodies against acetylated, maleylated and MDA-modified lipoproteins recognized antigens in human atherosclerotic aorta. Modified proteins were localized both intra- and extracellular in tectum, superficial and deep layers of the atherosclerotic lesions. The most typical mode of depositions for all modified proteins si represented by extracellular deposits in the cap of lipid streaks and fibrous plaques, especially in transitional “shoulder” area.The intimal deposits of modified proteins shared similar features with distribution of apo-B-containing lipoproteins, like as of lipids detectable by Oil Red staining. The areas where modified proteins and apo-B-containing lipoproteins were revealed did often coincide with foci of IgG deposits. Modified proteins were not detectable in the non-affected segments of aortic intima.